A catalytic alloy approach for graphene on epitaxial SiC on silicon wafers. Issue 5 (5th February 2015) - Iacopi, Francesca; Mishra, Neeraj; Cunning, Benjamin Vaughan; Goding, Dayle; Dimitrijev, Sima; Brock, Ryan; Dauskardt, Reinhold H.; Wood, Barry; Boeckl, John
Abstract: Abstract : We introduce a novel approach to the synthesis of high-quality and highly uniform few-layer graphene on silicon wafers, based on solid source growth from epitaxial 3C-SiC films. Using a Ni/Cu catalytic alloy, we obtain a transfer-free bilayer graphene directly on Si(100) wafers, at temperatures potentially compatible with conventional semiconductor processing. The graphene covers uniformly a 2″ silicon wafer, with a Raman I D / I G band ratio as low as 0.5, indicative of a low defectivity material. The sheet resistance of the graphene is as low as 25 Ω/square, and its adhesion energy to the underlying substrate is substantially higher than transferred graphene. This work opens the avenue for the true wafer-level fabrication of microdevices comprising graphene functional layers. Specifically, we suggest that exceptional conduction qualifies this graphene as a metal replacement for MEMS and advanced on-chip interconnects with ultimate scalability.